2018
DOI: 10.1002/oby.22339
|View full text |Cite
|
Sign up to set email alerts
|

Central Obesity Increases the Risk of Gestational Diabetes Partially Through Increasing Insulin Resistance

Abstract: Objective This study examined the associations of central obesity measures, waist to hip ratio (WHR) and waist circumference (WC), in early pregnancy with subsequent risk of gestational diabetes mellitus (GDM) and evaluated the potential mediating role of insulin resistance markers. Methods Within the prospective Pregnancy Environment and Lifestyle Study cohort of 1,750 women, WC and hip circumference were measured at gestational weeks 10 to 13. In a nested case‐control study within the cohort, 115 GDM cases a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 41 publications
2
42
0
Order By: Relevance
“… 28 29 A recent study found that central obesity was strongly associated with IR, which was calculated by HOMA-IR, and increased the risk of gestational diabetes in early pregnancy. 30 Alptekin et al indicated that in women with BMI>25.95 kg/m 2 and HOMA-IR>2.08 during pregnancy, weight loss may help reduce the risk of GDM. 31 An observation has demonstrated that during the first pregnancy trimester, HOMA-IR>2.60 can predict GDM.…”
Section: Discussionmentioning
confidence: 99%
“… 28 29 A recent study found that central obesity was strongly associated with IR, which was calculated by HOMA-IR, and increased the risk of gestational diabetes in early pregnancy. 30 Alptekin et al indicated that in women with BMI>25.95 kg/m 2 and HOMA-IR>2.08 during pregnancy, weight loss may help reduce the risk of GDM. 31 An observation has demonstrated that during the first pregnancy trimester, HOMA-IR>2.60 can predict GDM.…”
Section: Discussionmentioning
confidence: 99%
“…From the included studies, 2,226 and 25,449 pregnant women were GDM and non-GDM, respectively. A total of seven studies were from non-Asian countries [14,[16][17][18][20][21][22], and four were from Asia [13,15,19,23].…”
Section: Characteristics and Quality Assessment Of Includedmentioning
confidence: 99%
“…In these studies, nine studies reported the relationship between maternal central obesity and GDM in the first trimester [13][14][15][16][18][19][20][21] and two reported the relationship in the second trimester [22,23]. Six studies adopted WC or WHR [13][14][15][16][17][18], two used visceral adipose tissue depth (VAT) [20,21], two used BFI or FMP [22,23], and one used maternal SFT to measured maternal central obesity [19]. Most studies matched or adjusted for maternal age (n = 10) and BMI (n = 9).…”
Section: Characteristics and Quality Assessment Of Includedmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in the number of people with obesity is a global public health concern, which poses a substantial socioeconomic burden. Furthermore, epidemiologic studies have indicated that obesity increases the risk of diabetes, insulin resistance, metabolic syndrome, and cardiovascular disease [21,22]. Many studies in humans have shown that obesity associates with disturbances of biological rhythms, such as those governing sleep and food intake.…”
Section: Circadian Rhythm In Obesitymentioning
confidence: 99%